Abortive γδTCR rearrangements suggest ILC2s are derived from T-cell precursors - Shin, Samuel B. (Blood Adv, 2020)
Innate lymphoid cells (ILCs) are a recently identified subset of leukocytes that play a central role in pathogen surveillance and resistance, modulation of immune response, and tissue repair. They are remarkably similar to CD4(+) T-helper subsets in terms of function and transcription factors required for their development but are distinguished by their lack of antigen-specific receptors. Despite their similarities, the absence of a surface T-cell receptor (TCR) and presence of ILCs and precursors in adult bone marrow has led to speculation that ILCs and T cells develop separately from lineages that branch at the point of precursors within the bone marrow. Considering the common lineage markers and effector cytokine profiles shared between ILCs and T cells, it is surprising that the status of the TCR loci in ILCs was not fully explored at the time of their discovery. Here, we demonstrate that a high proportion of peripheral tissue ILC2s have TCRγ chain gene rearrangements and TCRδ locus deletions. Detailed analyses of these loci show abundant frameshifts and premature stop codons that would encode nonfunctional TCR proteins. Collectively, these data argue that ILC2 can develop from T cells that fail to appropriately rearrange TCR genes, potentially within the thymus.